Text Clustering as a Strategy to Develop EFL Language Learners’ Literary Competence - Bernal-Vargas, Andres Ivan (Íkala, Revista de Lenguaje y Cultura, 2018)
Reading and writing are two complex academic processes for foreign language learners. These processes can be integrated through text clustering (TC) as a language teaching strategy. This article reports on an action research with a mixed-methods design that implemented TC to developing reading, writing and literary competence in 33 young French language learners (22 years old average) in a B. A. in Foreign Languages programme at a Colombian university. The study was conducted for two years. Initially, a documentary analysis of four French courses syllabi was carried out, confirming that neither objectives nor contents of the literature component were explicitly stated. In addition, an entrance and exit surveys were administered to identify previous and final knowledge on basic narration features. During the pedagogical intervention, TC (two short stories and a film) was implemented so that the students could identify genre (narration) particularities following Larivaille (1974) and Hamon (1991) and produce narrative texts. It is concluded that TC was effective, first, because it allowed to integrate a literary component in the French language course for B1 level learners, and second, because most students improved narrative reading and writing.